Aprendizaje cooperativo en un curso virtual diseñado para docentes : un enfoque cualitativo - Pomajambo Zambrano, Mario Aurelio (2015)
This researching is presented with the interest of knowing How does the cooperative learning is developed in a virtual course which is taken by teachers according to analysis in interactions between participants? For that purpose the constructivism theory was taken account with the intention to find fundaments of the sociocultural theory of learning, to base the principles on regulate learning between peers and learning with help from the technology. From these aspects, the framework of the cooperative learning in virtual environment is hold. For this study were used theory such as the category system, subcategory and proposal definitions which were proved by Suárez (2012) The methodology was a case study, considering that our purpose has not been to make a statistic generalization, otherwise a theory generalization. It means, increase the cooperative learning theory in a new context, it is a virtual course where the participants are teachers, and it is presented by a university. To collect information we took into account the interactions between participants who participated during two weeks in a forum in the virtual course. This researching used the content analysis technique in order to gather and process information because we would pretend to know the meanings that contained the participants’ communication in the virtual course. The forums got sufficient stored data for that reason we used a kind of software QAD which is called Atlas.ti with which the coding process made, thus it obtains a report of more than one thousand meetings. Finishing this process, we used a system of matrixes to do the analysis. With the last result we obtained the summary from thirty nine analysis to five analysis, one per each subcategory of our study. To end, with the interpretation of the information from the point of view of our framework, it presented the results and recommendations took into account in this researching.